EFFECT OF COMPETENCE, LEADER-MEMBER EXCHANGE AND TEAMWORK ON WORK DISCIPLINE, JOB STRESS AND THEIR IMPACT ON EMPLOYEE PERFORMANCE OF CONSTRUCTION COMPANY IN EAST JAVA, INDONESIA - Suprawa T.A.; Brahmasari I.B.; Brahmaratih I.A. (Russian Journal of Agricultural and Socio-Economic Sciences, 2018)
Companies participating in an increasingly competitive world require strong employee support to build their long-term competitiveness. Therefore, performance should be a strategic value for the company. This study aims to evaluate the effect of competence, leader-member exchange and teamwork on work discipline, job stress and their impact on employee performance of Construction Company in East Java. The research method was quantitative approach with the sample of 230 respondents. Data were analyzed with Structural Equation Modeling using Amos 20.0 software. The results of this research show that competence has a significant influence on work discipline, but has no influence on job stress and performance. Leader-member exchange has a significant influence on work discipline, job stress, and employee performance. Teamwork has a significant influence on work discipline, but has no influence on job stress and employee performance. Work discipline and job stress have a significant influence on employee performance of Construction Company in East Java.